A rare diarrheic parasite in a kidney transplant patient: Cystoisospora belli. Issue 1 (9th January 2020) - Marques, Joana; Menezes, Maria; Mendes, Filipa; Dutra, Eduardo; Saiote, Joana; Santos, Sara; Cotovio, Patrícia; Caeiro, Fernando; Carvalho, Dulce; Nolasco, Fernando
Abstract: Cystoisospora belli colitis is a rare complication of immunosuppression in solid organ transplant recipients. We describe a case of Cystoisospora belli infection with colitis following renal transplantation.